(untitled) (Hasanuddin Civil and Bussiness Law Review, 2024)
Increased trade and investment, including e-commerce, also has the potential to increase disputes. Business Dispute Resolution requires prompt and confidential means. Alternative dispute resolution onlin (online or internationally known as Online Dispute Resolution (ODR). Seeing the development of ODR as a business dispute resolution, especially e-commerce, in the international scope including in Asian countries, the question arises what about the development of ODR in Indonesia. This paper uses normative research methods with conceptual and legislative approaches, with primary and secondary legal materials through literature studies. ODR has been used as a business dispute resolution mechanism in Indonesia in several fields, although not quite a lot. The opportunity is even greater if Indonesia can form an ODR system as a form of Indonesia’s commitment as an ASEAN country within the framework of ASAPCP 2016-2025. There are quite a lot of ODR service providers, either separate or integrated with E-commerce platform.